Song and dance man - Ackerman, Karen; Gammell, Stephen (New York : Dragonfly books, 1992)
Grandpa demonstrates for his visiting grandchildren some of the songs, dances, and jokes he performed when he was a vaudeville entertainer.
Wilson's Children, November 1996
Elem. School Library Collection, June 2000
Notable/Best Books (A.L.A.), September 2000
School Library Journal, August 2000
Book Links (A.L.A.), March 2007
Horn Book, October 2003
Keywords: Entertainers -- Fiction; Grandfathers -- Fiction; Entertainers -- Fiction; Grandfathers -- Fiction